International Inequality and the COVID-19 Pandemic - Michael Dauderstädt (Intereconomics)
Abstract The lockdowns and stimulus programmes that governments have adopted to fight the COVID-19 pandemic and the associated economic crisis have affected the distribution of income and production within and between countries. Considering both, current evidence indicates that the EU-wide and global inequality of disposable income did not change dramatically in 2020. However, the unequal impact on the wealth and health of people is likely to worsen income inequality in the future.